Beast [videorecording (DVD)] - Pearce, Michael, 1977-; Buckley, Jessie, 1989-; Flynn, Johnny; James, Geraldine, 1950- (Lions Gate Entertainment, 2018)
A disturbed woman living in a secluded community finds herself pulled between the control of her overbearing family and the appeal of a secretive stranger suspected of a series of vicious murders.